PENGARUH BUADAYA ORGANISASIONAL, SELF-EFFICACY DAN LOCUS OF CONTROL TERHADAP KINERJA KARYWAN (STUDI PADA PT. SANGO CERAMICS INDONESIA) - Satria Oktaditya, 13.05.51.0095 (Students' Journal of Economic and Management, 2017)
This study aims to examine and analyze the influence of organizational culture, self-efficacy and locus of control to the desire to employee performance. The object of study in this paper is PT. Sango Ceramics Indonesia. The sampling technique in this research use the purposive sampling technique with the number of respondents is 75. Analysis of the data used include the product moment test validity, reliability testing with Alpha Cronbrach, multiple regression analysis, t test to test and aprove the research hypothesis. The results of the research are (1) organizational culture give positive and significant impact on the performance of the employee, the stronger organizational culture within the employee will improve employee performance. (2) self-efficacy give positive and significant impact on the performance of the employee, the stronger self-efficacy within the employee will improve employee performance. (3) locus of control give positive and significant impact on the performance of the employee, the stronger locus of control within the employee will improve employee performance. Keywords : Organizational Culture, Self-Efficacy, Locus Of Control and Employee Performance